2019
DOI: 10.2298/sos1901081i
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and corrosion properties of AlCu matrix hybrid composite materials

Abstract: In this study, AlCu matrix hybride composites with various ratios of boron carbide (B4C), hexagonal boron nitride (hBN), and graphite (Gr) were produced by using hotpressing method. The microstructure, density, mechanical and corrosion properties of these composites were investigated. Optical microscopy, scanning electron microscopy, and X-ray diffraction were used to characterize the microstructures, and the experimental densities of the composites were measured using a helium pycnometer. The mechanical prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Several factors cause a growth in hardness. The hardness of the composite elements, the dispersion strengthening effect and the effect of the hard particles on the movement of dislocations, depending on the mixture rule [25,26]. Since the composite layers are harder than the middle layer, the wear resistance of the composite layers is expected to increase.…”
Section: Methodsmentioning
confidence: 99%
“…Several factors cause a growth in hardness. The hardness of the composite elements, the dispersion strengthening effect and the effect of the hard particles on the movement of dislocations, depending on the mixture rule [25,26]. Since the composite layers are harder than the middle layer, the wear resistance of the composite layers is expected to increase.…”
Section: Methodsmentioning
confidence: 99%
“…H c = H m f m + H r f r where H c is the hardness of the alloy, H m is the hardness of the matrix, H r is the hardness of the reinforcement element, and f m , f r are the volumetric ratios of the matrix and the reinforcement element, respectively. Hard particles prevent the dislocation movement and increase the strength of the HEAs [37,38]. 4) HEA+TiC (15 wt%), ( 5) HEA+WC (5 wt%), ( 6) HEA+WC (10 wt%), ( 7) HEA+WC ( 15wt%), and (8) HEA+TiC (5 wt%)+WC (5 wt%).…”
Section: (A (B ) (C) (D ) (E) (F) (G ) (H )mentioning
confidence: 99%
“…If only the casting method is used in the production of the Al matrix and B 4 C type reinforcement composite, secondary sintering could be applied to achieve good distribution and wettability [30]. However, the hot pressing method is an effective method to attain good wettability and distribution of composite particles, which in turn lead to enhanced mechanical [31] and wear [32] properties. Kaner reported that materials having high surface energy should be used for good wettability.…”
Section: Microhardness and Tribological Testsmentioning
confidence: 99%